Association of echocardiographic pulmonary hypertension with all-cause mortality in hospitalized AECOPD patients - Zhiqi Zhao; Xue He; Ruoyan Xiong; Yanan Cui; Weiwei Meng; Jiankang Wu; Jiayu Wang; Rui Zhao; Huihui Zeng; Yan Chen (International Journal of Cardiology: Heart & Vasculature)
Background: Chronic obstructive pulmonary disease (COPD) often coexists with pulmonary hypertension (PH). However, whether pulmonary artery pressure (PAP) or even suspected PH assessed by echocardiography during acute exacerbation stage predicts mortality after discharge is unclear. Methods: We conducted an retrospective study of hospitalized patients with acute exacerbation of COPD (AECOPD). Peak tricuspid regurgitation velocity (TRV) and additional variables were used to assess PH risk. Results: Cox regression analysis showed that echocardiographic suspected PH was the independent risk factor for the significantly increased long-term mortality (adjusted HR 1.64; 95% CI 1.06–2.53) after discharge in AECOPD patients. Logistic regression analysis revealed a negative correlation between blood eosinophil (EOS) counts at admission and the prevalence of suspected PH (adjusted OR 0.18; 95% CI 0.04–0.89). Triple therapy (adjusted HR 0.18; 95% CI 0.05–0.61), neither LABA/ICS during stable stage was associated with a significant reduction in long-term mortality in hospitalized AECOPD patients with suspected PH. Conclusion: Echocardiographic suspected PH was associated with adverse survival in hospitalized AECOPD patients. Low EOS counts at admission emerged as a potential biomarker for elevated estimated systolic PAP. Triple therapy during stable stage was associated with a significant reduction in long-term mortality in AECOPD patients with suspected PH.